Pusat Pelatihan Jasa Bangunan Di Pekanbaru Berdasarkan Prinsip Desain Ludwig Mies Van Der Rohe - Nadine Raraz Cahyani; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Indonesia provides many types of services users, but there are still many service workers who still do not have jobs due to lack of experience. One of them is construction services, which is a voice in the construction workforce profile in LPJK (2015), the number of uncertified construction workers in Riau Province reaches 124,158 people. They need a forum for construction workers to be trained and educated by giving them special skills in the not too long time and producing concrete evidence in the form of certification. For this reason, this training center is needed to accommodate workers who still lack the experience to train themselves, and improve work competency with the skills they have chosen. The training center has the concept of regularity with the principles of Ludwig Mies Van Der Rohe who prioritizes the function and simplicity of form. Keyword: Building services training center, Regularity